Steepest descent method for uncertain multiobjective optimization problems under finite uncertainty set - Kumar S.; Ansary M.A.T.; Mahato N.K.; Ghosh D. (My University, 2025)
In this paper, a steepest descent method is developed for the robust counterpart of uncertain multiobjective optimization problems under finite uncertainty. The robust counterpart under consideration is the minimum of objective wise worst case, which is a nonsmooth deterministic multiobjective optimization problem. To solve this robust counterpart with the help of the steepest descent method, a subproblem is constructed and solved to find a descent direction. An Armijo-type inexact line search technique is employed to find a suitable step length. With the help of the descent direction and step length, a sequence is generated. The convergence of the proposed method is justified under some common assumptions. Finally, the algorithm is verified and compared with one existing method with the help of some numerical problems. © 2024 Informa UK Limited, trading as Taylor & Francis Group.